The religious and spiritual beliefs and practices of mental health educators: a national study - Polson, Edward C. (Journal of spirituality in mental health, 2026)
Currently, little is known about the religious and spiritual (RS) beliefs and practices of faculty in graduate mental health training programs. Here, we analyze data from a recent survey of 1,956 faculty in accredited counseling, marriage and family therapy, psychology, and social work programs across the U.S. to provide the first national assessment of RS beliefs and practices of faculty in these disciplines. Results indicate that many hold RS beliefs and practices suggesting potential openness to training graduate students on the effective integration of clients’ RS in mental health treatment. However, we also find significant variation across disciplines.